TANTANGAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP INDIKATOR PEMAHAMAN DAN CAPAIAN KOMPONEN MANAJEMEN SEKOLAH - Nunun Masnunah; Chaerul Rochman; Karman Karman (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
This research aims to find out one of the components to improve the quality of education, namely the school management component, to know the achievement of school management, namely through the understanding of PAI teachers and non-PAI teachers as respondents on each indicator. The population in this study is a unit of junior high school education / Mts. The research method used is descriptive quantitative. The instrument used is a questionnaire or questionnaire about understanding the components of school management. Data retrieval is done using google form that is distributed to 7 PAI teachers and 7 non-PAI teachers. The conclusion of this study is that the understanding between PAI teachers and non-PAI teachers has a high level of understanding, both of which show good understanding despite the thin differences, and there are indicators that are still lacking and need to be improved on the understanding of school management. PAI teachers and non-PAI teachers should be able to improve their knowledge in improving the quality of education.